Optimization of Medical Equipment Inventory Management Through Barcode-Based Digitalization - Maria Indah Septirini; Tuti Afriani; La Ode Abdul Rahman; Krisna Yetti; Dyah Fitri Wulandari (Indonesian Journal of Global Health Research, 2026)
Digital transformation in medical equipment logistics is a vital part of healthcare reform, aiming to enhance efficiency, accuracy, and patient safety. One of the main challenges at hospital is the manual documentation system for borrowing and returning medical equipment, which results in low accountability, service delays, and a high risk of equipment loss. : Case report area focused on the HCU/PICU unit. This study aims to describe the implementation process of a barcode-based digital medical inventory system through a managerial approach and planned change intervention based on Kurt Lewin's theory. A case report was conducted using Kurt Lewin’s planned change approach (unfreezing, moving, and refreezing), data analysis through observation, questionnaires, interviews, and implementation evaluation. The Assessment of Medical Equipment Management (MEM) questionnaire administered to 103 nurses revealed that 87.4% of units still use manual recording and 50.98% reported suboptimal coordination in equipment returns, with reliability  0.86 and validity loading factor ±0.5; content validity 85%. The intervention involved developing Standard Operating Procedures (SOPs) and technical guidelines for the "MedScan-KISA" barcode system, conducting simulation trials using Google Forms and barcode scanners, and directly supervising the implementation process. The implementation of a barcode-based digital inventory system in the HCU/PICU unit of hospital was carried out through a gradual change process based on Kurt Lewin’s theory. In the unfreezing phase, problems with the manual inventory system were identified through interviews, observations, and cross-unit discussions, leading to the design of a simple digital inventory system for the HCU/PICU unit. In the moving phase, an SOP was developed, simulations using barcodes and Google Forms were conducted, and intensive socialization and mentoring were provided to staff. Finally, in the refreezing phase, the new system was consistently practiced and integrated into daily routines in the HCU/PICU unit, thereby facilitating inventory recording and the return of medical equipment.